The dynamics of intense long-term motivation in language learning: Directed Motivational Currents in theory and practice - Muir, Christine (2016)
Directed Motivational Currents (DMCs) are a novel motivational construct which describe periods of highly motivated behaviour while working towards a well-defined and personally significant end goal (see e.g. Dörnyei, Henry & Muir, 2016). Such periods of motivation are found in diverse contexts and directed towards varied outcomes, yet are uniquely recognisable by the highly positive emotionality exhibited by individuals, who during this time often surpass even their wildest expectations. To date, DMC research has focused on qualitative accounts of the personal experiences of DMCs, and while this has offered a wealth of comprehensive data, key research strands remain unexplored. In response to this, this thesis comprises two complementary studies, each looking at a novel aspect of DMC theory and application.